Chapter Optimization of the Synthesis Procedures of Graphene and Graphite Oxide - Luis Valverde Palomino, José (InTechOpen, 2016)
The optimization of both the chemical vapor deposition (CVD) synthesis method to prepare graphene and the Improved Hummers method to prepare graphite oxide is reported. Copper and nickel were used as catalysts in the CVD-graphene synthesis, CH4 and H2being used as precursor gases. Synthesis variables were optimized according to a thickness value, calculated using a homemade Excel-VBA application. In the case of copper, the maximum thickness value was obtained for those samples synthesized at 1050°C, a CH4/H2 flow rate ratio of 0.07 v/v, a total flow of 60 Nml/min, and a time on stream of 10 min. In the case of nickel, a reaction temperature of 980°C, a CH4/H2 flow rate ratio of 0.07 v/v, a total flow of 80 Nml/min, and a time on stream of 1 min were required to obtain a high thickness value. On the other hand, the Improved Hummers method used in the synthesis of graphite oxide was optimized. The resultant product was similar to that reported in literature in terms of quality and characteristics but both time and cost of the synthesis procedure were considerably decreased.